2019
DOI: 10.1159/000497789
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Ultrasound Reports: Deficiencies and Recommendations

Abstract: Objective: Thyroid ultrasound plays a major role in the clinical management of patients with thyroid nodules. Comprehensive reporting enables malignant risk stratification and biopsy decisions. In this study, we aimed at a systematic evaluation of the content and completeness of thyroid radiology reports. Methods: A retrospective study was undertaken. A total of 200 thyroid ultrasound reports of examinations performed over a 1-year period were reviewed. After excluding 18 reports, the remaining 182 were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(30 reference statements)
0
3
0
4
Order By: Relevance
“…There are a limited number of studies that critically evaluate the content of ultrasound scans reported by radiologists [19]. In our literature research, we could not nd a similar study that systematically evaluated breast ultrasound reports in terms of technical features, content and results.…”
Section: Discussionmentioning
confidence: 89%
“…There are a limited number of studies that critically evaluate the content of ultrasound scans reported by radiologists [19]. In our literature research, we could not nd a similar study that systematically evaluated breast ultrasound reports in terms of technical features, content and results.…”
Section: Discussionmentioning
confidence: 89%
“…Ayrıca kılavuzlarda yer alan nodül boyutu ile ilgili olarak yapılan kategorik sınıflamalardan esinlenerek nodül boyutu bakımından hastalar iki farklı cut-off değerleri kullanılarak kategorik gruplara ayrılmıştır; 0-19 mm ve ≥20 mm olarak iki grupta ve ayrıca 0-9 mm, 10-19 mm, 20-29 mm ve ≥30 mm olarak dört kategorik grupta ayrı ayrı değerlendirilmiştir. [1][2][3][4][5][6] 1,12,14 Bazı yayınlarda ise kılavuzlar arasında uyumsuzluk olması nedeniyle hastaların yönetiminde sorunlar olabileceği bildirilmektedir. 1 Nodüllerin çoğunlukla benign olması, malign olanlarının ve özellikle de 1 cm'den küçük olanlarının agresif olmayan yavaş bir seyir göstermesi düşüncesiyle bazı yayınlarda, saptanan bütün nodüllerin İİA ile değerlendirilmesinin gerekli olmadığı bildirilmektedir.…”
Section: Yöntemunclassified
“…8,11 İİA ile daha ileri inceleme gerekip gerekmediğine ise ATA, ETA ve diğer sık kullanılan rehberler eşliğinde hem sonografik özelliklere hem de nodül boyutuna bakılarak karar verilmektedir. 1,12,14 Bazı yayınlarda ise kılavuzlar arasında uyumsuzluk olması nedeniyle hastaların yönetiminde sorunlar olabileceği bildirilmektedir. 1 Nodüllerin çoğunlukla benign olması, malign olanlarının ve özellikle de 1 cm'den küçük olanlarının agresif olmayan yavaş bir seyir göstermesi düşüncesiyle bazı yayınlarda, saptanan bütün nodüllerin İİA ile değerlendirilmesinin gerekli olmadığı bildirilmektedir.…”
Section: Introductionunclassified
See 2 more Smart Citations